Enforcement of the Principle of Legality to Living Law as Legal Basis in the Positivism of Displacement Customary Law - Manalu, Juita; Anggusti, Martono; Tambunan, Debora (Manunggal Halim Jaya, 2024)
Living law is an inseparable part of the Indonesian criminal law system. However, in perspective of legality principle, living law causing pros and cons. The idea of regulating the living law in Indonesian, as the basis for criminal prosecution, for unregulated act is still debated. The issue that will be analysed in this article is how to apply living law/adat law as a basis for prosecuting criminals related to the existence of legality principle and, how to measure the enforcement of living law in criminal process. Based on the analysis using the principle of legality, it can be concluded that living law, as basis for prosecution, is contrary to principle of legality and protection of human rights. The enactment of living law can potentially create legal uncertainty and abuse of power by the government. Law enforcement against living law is also difficult to implement, because it is tied to the four indicators. Therefore, the living law provision better not be placed as part of general principles in the Indonesian Penal Code Bill. Keywords: Code Bill: Legality principle; Living law.